Iskolai kiadási egyenlőtlenségek - 1992 - 2005 - Zoltán Hermann (Hungarian Academy of Sciences, Institute of Economics, 2007)
– The paper analyses disparities in local education expenditures at the settlement and school level n Hungary. It is shown that local average income, which is a major element of the local government budget constraint, has a strong impact on school expenditures, especially in towns. This lack of fiscal neutrality implies that settlements with a higher share of socially disadvantaged children spend somewhat less on education. In case of towns, this between settlement effect is offset by within settlement disparities in expenditures: schools with relatively more disadvantaged pupils tend to have a larger budget compared to other schools of the same town. Considering village and town schools together indicates, that the higher is the share of poor children in a school, the lower are per capita expenditures on average. Though the magnitude of the effect is small, it reveals a fundamental equity problem. While the successful education of disadvantaged pupils might require substantial additional resources, the pubic education system in Hungary can not provide school with these resources now.
Keywords: 330; School expenditures; interjurisdictional disparities; wealth neutrality of education expenditures; Bildungsfinanzierung; Schulfinanzierung; Ungarn